Analisis Ketersediaan, Kondisi, dan Penggunaan Media Pembelajaran IPA di SDN 41 Mallari Kecamatan Awangpone Kabupaten Bone - Sri Yulisnaeni; Muliadi Muliadi; Sudarto Sudarto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This research is a type of qualitative descriptive research that aims to determine the availability, condition, and use of science learning media at SDN 41 Mallari, Awangpone District, Bone Regency. The subjects in this study were teachers of grades I, II, III, IV, V, and VI. Data collection is done by observation, interviews, and documentation. Data reduction analysis techniques, data display, and conclusion drawing/verification. The results of this study indicate that the availability of science learning media is not fully available in accordance with the standard in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 23 of 2013 concerning Minimum Service Standards for Basic Education in Districts/Cities and eleven types according to the scope of science learning materials in elementary schools. Most of the science learning media are in a damaged condition, both the complete and incomplete available media, and the absence of special officers who take care of the science learning media makes the media unmanageable, with the availability of damaged learning media and incomplete components making the media can not be used.